Standard handbook of hazardous waste treatment and disposal (New York, 1997)
The book provides the most comprehensive and current information available on hazardous waste management, site cleanup, and treatment alternatives. It also presents the latest information on new and proposed federal hazardous waste legislation, a great emphasis on waste minimization and pollution prevention techniques, and expanded coverage of leading-edge treatment disposal and remediation technologies
Keywords: hazardous wastes - management - handbooks, manuals, etc